Potential for sustainable utilisation of agricultural residues for bioenergy production in Pakistan: An overview. (10th March 2021) - Abdullah, Aisha; Ahmed, Ashfaq; Akhter, Parveen; Razzaq, Abdul; Hussain, Murid; Hossain, Nazia; Abu Bakar, Muhammad Saifullah; Khurram, Shahzad; Majeed, Khaliq; Park, Young-Kwon
Abstract: Pakistan's current energy portfolio is problematic due to a lack of proper management and implementation of appropriate energy policies. This densely populated country has a high energy demand that rises yearly and is expected to increase three-fold by 2050. However, fossil fuel resources are continuously depleting by global overuse while negatively impacting the environment through increasing greenhouse gas emissions. This study reviewed the potential for agricultural residues to be used as renewable energy sources for bioenergy production in Pakistan to address the energy-related challenges that would also help in addressing the economic and environmental concerns. First, a comparison was made between the current energy situation, potential renewable energy scenarios, and global trends. Second, greenhouse gas (i.e., CO2 ) emissions in Pakistan were summarised and compared with other regions. Third, the thermochemical properties of different agricultural residues were reviewed along with varying the options of processing to produce renewable energy such as thermochemical conversion approaches (combustion, pyrolysis, gasification, and liquefaction) and biochemical conversion options (anaerobic digestion, and fermentation). Pakistan being an agricultural-based economy, produces vast quantities of agricultural residue biomass, which is mostly underutilized as animal feed, conventional fuel substitutes, left to rot in fields or burnt to get rid, resulting in the vast emissions of greenhouse gases causing severe environmental pollution and smog formation. A considerable share of Pakistan's national energy demand can be fulfilled if these feedstocks are adequately managed and exploited through the energy sector and converted into large-scale bioenergy. Highlights: The potential utilisation of agri-residues for energy production is reviewed. Pakistan's energy scene is problematic, expected to rise to 142 MTOE by 2025. Country is meeting only 15% of its energy needs from indigenous resources. Energy recovery from residues can contribute effectively if managed properly. Agri-residues have a potential to generate ∼4.4 million m 3 /d of syngas annually.